In quest of empowerment : the Grameen Bank impact on women's power and status - Mizan, Ainon Nahar (Dhaka : University Press, 1994)
Impact on socio-economic and political status of women in Bangladesh; study of two villages, Dewannagar in Hathazari and Hetalia in Patuakhali districts.
BIED
Keywords: Grameen Bank; Rural credit -- Bangladesh -- Dewannagar; Rural credit -- Bangladesh -- Hetalia